The Causal Relationship Between Economic Growth and Export: The Case of Russia - Özgür Uysal; Sultan Sat (İstanbul İktisat Dergisi)
The relationship between economic growth and export has been one of the most disputed issues in economics literature. The main objective of this paper is to find the direction of the causality relationship between economic growth and export in Russia. We performed our analysis using quarterly economic growth and export data from 2003:q1 to 2018:q4. Using the ADF unit root test for stationarity we first analyzed whether the variables contained a unit root. As a result, we determined that all the variables were stationary at their first differences. Subsequently, we conducted the Engle Granger Cointegration test to analyze the long term relationship between the variables and we determined that there was a long-term relationship between the variables. By using the Granger Causality Test to determine the direction of the relationship, we found that a unidirectional causality existed between economic growth and export in the Russian economy between 2003 and 2018. As seen in the causality relationship between economic growth and export being unidirectional (from export to growth), the effect of export on economic growth is dominant because of export’s dependence on raw materials. Russia should reduce its economic dependence on oil prices and strong structural improvements are necessary to reduce this dependence.